PEMBELAJARAN TAHFIDZ DENGAN METODE TALAQQI VIA APLIKASI ZOOM DAN WHATSAPP (STUDI KASUS SETORAN ONLINE RUMAH TAHFIDZ SMP MA'ARIF NU 1 WANAREJA) - Ainiyatul Latifah; Wiji Nurasih; Waliko; Mhd. Rasidin; Doli Witro (Universitas Muhammadiyah Prof Dr Hamka, 2021)
Since entering the beginning of 2020, the Covid-19 outbreak has rapidly spread to various parts of the world, including Indonesia. Therefore, everyone must keep their distance from each other to avoid transmission and break the chain of the virus. This situation requires the government to impose restrictions on community activities on a large scale, including in this case the restrictions on interaction in the education sector at the Tahfidz House of SMP Ma'arif NU 1 Wanareja. All learning activities must be transferred to the online system (online) or online, as well as the student's tahfidz program. Deposits for memorizing Al-Qur'an which are usually done in talaqqi in front of ustadz/ustadzah are now made through Zoom and Whatsapp media. This study aims to provide an overview of how an effort to learn Al-Qur'an must always run even in very difficult conditions. The results of this study indicate that Zoom is used for interpretation learning which requires delivering presentations (video calls), while Whatsapp is used for memorizing deposits through voice notes.